In-service training needs of agricultural extension personnel associated with climate change adaptation in Malaysia - Umar, Sulaiman; Man, Norsida; Mohd Nawi, Nolila; Shuaibu, Hajara; Jega, Abdussalam Adamu; Saleh, Jassim Mohammed (University Community Transformation Centre, Universiti Putra Malaysia, 2017)
The study is aimed at describing the perceived importance of, and proficiency in, climate change related competencies among extension personnel; and evaluate the resultant training needs. The study randomly sampled 328 extension personnel from six states of Malaysia. Cross-sectional data was collected using structured questionnaire that was reviewed and pre-tested for validity and reliability. Analysis was conducted using SPSS. Descriptive statistics including the mean weighted discrepancy score were employed in the analysis. The Borich’s Needs Assessment Model was adopted for the study. On a scale of 5, the most important perceived climate change competency items are: communicating climate information effectively (M=4.73, SD=0.75), using ICTs in climate change adaptation (M=4.70, SD=0.53), and promoting eco-friendly agronomic practices and farming system (M=4.67, SD=0.61). The competencies with the highest proficiency scores were: promoting cultivation of improved crop varieties (M=2.43, SD=0.77), planning climate resilient development (M=2.33, SD=0.80), capacity to build linkages among stakeholders (M=2.33, SD=0.76). Training needs for extension personnel are highest in: communicating climate information effectively (MWDS=12.49), use of ICTs in adaptation (MWDS = 12.22), promotion of eco-friendly practices and systems in agriculture (MWDS = 11.67), and impact of climate change on urban development (MWDS=11.19). The study evaluated the gap between what extension workers know and what they should know in issues of climate change to facilitate adaptation. It is recommended that any training programme in the area should prioritize these competencies to enhance personnel capacity as they tackle climate change in collaboration with the farmers.